Perlakuan Air Kelapa Tua, Dan BAP Pada Media MS, VW Terhadap Protocorm Anggrek Dendrobium sp. Secara Kultur In vitro - Sundalangi, Grace; Mandang, Jeany; Sompotan, Saartje (Sam Ratulangi University, 2023)
This study aims to obtain accurate results from the concentration of old coconut water and BAP on Vacin and Went and Murashige and Skoog media on the growth of Dendrobium sp. through in vitro culture. The method used in this study was a completely randomized design consisting of 8 treatments and 8 replications. Each replication consisted of 2 bottles so that a total of 128 bottles, namely A0 (control, without using old coconut water), A1 (12.5% old coconut water), B0 (control, without using BAP), B1 (BAP 0.5 mg/L ), and used 2 types of media (Murashige and Skoog) and (Vacin and Went). The variables observed included the number of protocorm, wet weight, dry weight, and pH of the media. The results showed that the concentration of old coconut water and BAP had a significant effect on the number of protocorm, fresh weight, and pH of the media on Dendrobium sp. The best treatment obtained was VA1B1 (12.5% old coconut water, 0.5 ppm BAP) with a media pH of 5.0 V A1B1, the number of protocorm V A1B1 49.57, and VA1B1 0.008 g which had the best results compared to other treatments.